A Report on North South Experiences of Doctoral Training for Development in Africa - Hennessy, Martina (My University, 2012)
‘North-South Experiences of Doctoral Training for Development in Africa’ is a study of three models of partnership between Trinity College Dublin (TCD) and higher education institutes in six African countries. The goal of these partnerships is to deliver collaborative doctoral training programmes in global health, natural sciences and economics, to train researchers and build research and teaching capacity in African institutions. The programme is co-funded by Irish Aid under the Programme for Strategic Cooperation (PSC) between Irish Aid and Higher Education and Research Institutes 2007-11. This study evaluates the three models employed in the Irish Aid/HEA project titled “Doctoral Training for Development in Africa” in order to understand the strengths and weaknesses of the three different doctoral training models, capture lessons learnt from our partnerships and make recommendations to others who wish to establish North-South doctoral training programmes.
Keywords: Immunology, Inflammation & Infection; International Development